Pengaruh Reference Group, Reasonable Price, Dan Perceived Usefulness Terhadap Online Purchase Intention Produk Ipad - Sulthan Dhia Yafi Muhammad; Donant Alananto Iskandar (Research and Community Service UNIVERSITAS KALBIS, 2025)
This study aims to examine the influence of Reference Group , Reasonable Price, and Perceived Usefulness on Online Purchase Intention toward iPad products among consumers in Indonesia. In the growing digital marketplace, consumers’ purchasing decisions are influenced by social factors, price perceptions, and the perceived benefits of a product. Therefore, understanding these determinants is important for companies seeking to increase consumers’ intention to purchase technology products online. This research employed a quantitative approach and involved 165 respondents selected through a purposive sampling technique. Data were collected using a structured questionnaire and analyzed through multiple regression analysis and hypothesis testing. The findings reveal that Reference Group , Reasonable Price, and Perceived Usefulness simultaneously have a significant positive effect on Online Purchase Intention. Consumers are more likely to purchase iPad products online when they receive positive recommendations from influential groups, perceive the price as fair and reasonable, and recognize the product’s usefulness in supporting their daily activities. These results provide valuable insights for marketers in developing effective marketing and pricing strategies to enhance consumers’ Online Purchase Intentions.